Foreign Exchange derivatives in india - Kumar, Prateek (2007)
As India is slowly but steadily marching towards the most prestigious crown of a global super power, itÃÂ¢ÃÂÃÂs because of the un segmented development in the country that it is attracting investments from international firms and in a large way. India is also growing its international trade as it is a land for cheap labour and provides cheap services and products to other countries at a bargain price. As there is rapid globalisation taking place the country should have a well developed foreign exchange market. it should be well regulated and have proper terms and conditions and easy accessibility. As exchange risk is considered to be the most the dangerous type of risk amongst the different types of financial risks, steps needs to be taken to guard people from the same. For this purpose their has to be a well developed derivative market, for and which should be used properly by all the sections of the public which need access to the foreign exchange market. This should be comparable to any of the developing countries like China.